REFLECTION UPON THE PRACTICE OF THE TEACHING OF NURSING IN OUR TIMES - Palencia, Esperanza (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The present day’s conception of nursing teaching has to adapt to the constant changes in our epoch. Its primordial aim should be promotion of the general understanding by pupils through cooperation and effective communication with the utilization of the shipwreck model, the theory and praxis dialectic and the practical critical rationality to achieve the contextualization of knowledge, leaving behind both the technological or positive model and the model of the astronaut. The necessity of change exists in nursing and includes the necessary curricular and educational structural changes in our universities enabling teachers to be more active in the set-up of educational programs effectively adapted to the particular conditions of a given context, like those of a hospital, a clinic, community or classroom. Accordingly encouragement should be given to constant academic actualization enabling the reﬂection about educational action and the real difﬁculties encountered in practical experience.